Odpowiedzi

2010-03-17T20:53:12+01:00
-2(3x+3)+2x=2x(2x-2)+3x
-6x-6+2x=4x2-4x+3x
-6x+2x-4x2+4x-3x=6
-7x-4x2=6

-(x+2)+2x+4=2(2x-4)
-x-2+2x+4=4x-8
-x+2x-4x=8+2-4
-3x=6
3x=-6
x=-6/3
x=-2

-6(3x-3)=-8(2x-2)
-18x+18=-16x+16
-18x+16x=16-18
-2x=-2
x=1

3(3x-3)=2x-7
9x-9=2x-7
9x-2x=-7+9
7x=2
x=7/2
x=3 i 1/2

2(2x+4)+3x=-(2x+4)+3
4x+8+3x=-2x-4+3
4x+3x+2x=-4+3-8
9x=-9
x=-1
2010-03-17T20:53:49+01:00
A.
-2(3x+3)+2x=2x(2x-2)+3x
-6x-6+2x=4x²-4x+3x /+6x+6-2x
4x²-4x+3x+6x+6-2x=0
4x²+3x+6=0
Δ=b²-4ac=3²-4*4*6=9-96<0 BRAK ROZWIĄZANIA

B.
-(x+2)+2x+4=2(2x-4)
-x-2+2x+4=4x-8
x+2=4x-8 /-x
2=3x-8 /+8
10=3x /:3
x=10/3=3 i 1/3

C.
-6(3x-3)=-8(2x-2)
-18x+18=-16x+16 /+18x
18=2x+16 /-16
2=2x /:2
x=1

D.
3(3x-3)=2x-7
9x-9=2x-7 /-2x
7x-9=-7 /+9
7x=2 /:7
x=2/7

E.
2(2x+4)+3x=-(2x+4)+3
4x+8+3x=-2x-4+3
7x+8=-2x-1 /+2x
9x+8=-1 /-8
9x=-9 /:9
x=-1
1 3 1
2010-03-17T21:19:45+01:00
-2(3x+3)+2x=2x(2x-2)+3x
-6x - 6 + 2x = 4x² - 4x + 3x
-4x - 6 = 4x² - x / +3x
-6 = 4x² + 2x
(niestety nie wiem jak to dokończyć, czy na pewno działanie jest dobrze przepisane?)

-(x+2)+2x+4=2(2x-4)
-x - 2 + 2x + 4 = 4x - 8
x + 2 = 4x - 8 / + 8
x + 10 = 4x / -x
10 = 3x / :3
x = 3 ⅓

-6(3x-3)=-8(2x-2)
-18x + 18 = -16x + 16 / +18x
18 = 2x + 16 / -16
2 = 2x / :2
x = 1

3(3x-3)=2x-7
9x - 9 = 2x - 7 / +9
9x = 2x + 2 / -2x
7x = 2 / :7
x = 2/7

2(2x+4)+3x=-(2x+4)+3
4x + 8 + 3x = -2x -4 + 3
7x + 8 = -2x - 1 / +2x
9x + 8 = -1 / -8
9x = -9 / :9
x = -1